Mitochondrial Molecular Abnormalities Revealed by Proteomic Analysis of Hippocampal Organelles of Mice Triple Transgenic for Alzheimer Disease - Yu, Haitao; Lin, Xuemei; Wang, Dian; Zhang, Zaijun; Guo, Yi; Ren, Xiaohu; Xu, Benhong; Yuan, Jianhui; Liu, Jianjun; Spencer, Peter S.; Wang, Jian-Zhi; Yang, Xifei (Frontiers in Molecular Neuroscience, 2018)
Mitochondrial dysfunction is implicated in the pathogenesis of Alzheimer's disease (AD). However, the precise mitochondrial molecular deficits in AD remain poorly understood. Mitochondrial and nuclear proteomic analysis in mature male triple transgenic AD mice (PS1M146V/APPSwe/TauP301L) by two-dimensional fluorescence difference gel electrophoresis (2D-DIGE) coupled with MALDI-TOF-MS/MS, bio-informatics analysis and immunofluorescent staining were performed in this study. In addition to impaired spatial memory impairment and intracellular accumulation of amyloid 1-42 (Aβ1-42) in the 3xTg-AD mice, a well-accepted mouse model of the human disease, we also found significantly increased DNA oxidative damage in entorhinal cortex, hippocampal CA1, CA3 and dental gyrus (DG), as evidenced by the positive staining of 8-hydroxyguanosine, a biomarker of mild cognitive impairment early in AD. We identified significant differences in 27 hippocampal mitochondrial proteins (11 increased and 16 decreased), and 37 hippocampal nuclear proteins (12 increased and 25 decreased) in 3xTg-AD mice compared with the WT mice. Differentially expressed mitochondrial and nuclear proteins were mainly involved in energy metabolism (>55%), synapses, DNA damage, apoptosis and oxidative stress. Two proteins were differentially expressed in both hippocampal mitochondria and nuclei, namely electron transport chain-related protein ATP synthase subunit d (ATP5H) was significantly decreased, and apoptosis-related dynamin-1 (DYN1), a pre-synaptic and mitochondrial division-regulated protein that was significantly increased. In sum, perturbations of hippocampus mitochondrial energy metabolism-related proteins responsible for ATP generation via oxidation phosphorylation (OXPHOS), especially nuclear-encoded OXPHOS proteins, correlated with the amyloid-associated cognitive deficits of this murine AD model. The molecular changes in respiratory chain-related proteins and DYN1 may represent novel biomarkers of AD.